The Relationship between Language and Ethnicity - Mishra, Dr. Gayatree (The journal of contemporary issues in business and government, 2022)
Language plays a crucial role in the construction and maintenance of ethnic identity. The ethnicity has a more striking relationship to language than other social factors such as gender, age, or social class. Thus language is only one factor in the ethno linguistic description of a people, or an ethnic group. Language is a primary characteristic and an always present characteristic of ethnicity. Without language you would have an incomplete description of ethnicity. Language is the primary component of ethnicity. What is ethnicity? Is there a 'white' way of speaking? Why do people sometimes borrow features of another ethnic group's language? Why do we sometimes hear an accent that isn't there? Drawing on research from a range of ethnic groups around the world, it shows how language contributes to the social and psychological processes involved in the formation of ethnic identity, exploring both the linguistic features of ethnic language varieties and also the ways in which language is used by different ethnic groups. Complete with discussion questions and a glossary, Language and Ethnicity will be welcomed by students and researchers in sociolinguistics, as well as anybody interested in ethnic issues, language and education, inter-ethnic communication, and the relationship between language and identity.